2017
DOI: 10.5216/ree.v19.41480
|View full text |Cite
|
Sign up to set email alerts
|

Higiene bucal no paciente internado em unidade de terapia intensiva: revisão integrativa

Abstract: A prevenção e a promoção da saúde bucal dos pacientes internados em uma unidade de terapia intensiva é responsabilidade da equipe de enfermagem. Revisão integrativa que teve o objetivo de identificar as contribuições das pesquisas produzidas por enfermeiros sobre os cuidados bucais aos pacientes internados nestas unidades. Selecionou-se 17 artigos publicados no período de 2010 a 2016 indexados no State National Library of Medicine (PubMed/MEDLINE) e na Biblioteca Virtual em Saúde (BVS). Os estudos foram catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
(70 reference statements)
0
13
0
8
Order By: Relevance
“…There is no standardized methodology that allows it. Nevertheless, those that aimed to compare the reduction of pneumonia incidence or microbial reduction, 12,14,16,18,19 didn't present statistically significant conclusion that the oral hygiene can reduce the incidence of aspiration pneumonia, except the study of Vidalet al 4 These results agree with a systematic review on oral hygiene and pneumonia in children in ICU 11 which concluded that there is no scientific evidence to support the use of oral hygiene isolated with chlorhexidine to prevent PVA. Overall, there are no well-established protocols that aim the best method of oral hygiene for children admitted to ICU.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There is no standardized methodology that allows it. Nevertheless, those that aimed to compare the reduction of pneumonia incidence or microbial reduction, 12,14,16,18,19 didn't present statistically significant conclusion that the oral hygiene can reduce the incidence of aspiration pneumonia, except the study of Vidalet al 4 These results agree with a systematic review on oral hygiene and pneumonia in children in ICU 11 which concluded that there is no scientific evidence to support the use of oral hygiene isolated with chlorhexidine to prevent PVA. Overall, there are no well-established protocols that aim the best method of oral hygiene for children admitted to ICU.…”
Section: Discussionmentioning
confidence: 84%
“…The Table 2 presents a summary of the 12 selected studies and the classification given in accordance with the levels of evidence. [8][9][10][11] it is important to note the vast heterogeneity of The trials had evidence levels I, II, or III according to the rating scale for assessing the quality of randomized clinical trials. The twelve articles that fully or partly filled the inclusion criteria inclusion were randomized clinical trials, four presented allocation concealment, eight reported masking, two cited confounding factors, seven mentioned losses in…”
Section: Resultsmentioning
confidence: 99%
“…Although oral care is part of the routine nursing care, publications on the topic by Brazilian nurse researchers are developing. In fact, most of the available evidence is produced by international researchers (Nogueira & Jesus, 2017). Besides, there is so far no national survey on oral care and its conditions in Brazilian hospitals, hence the need to know the different realities of the country.…”
Section: Introductionmentioning
confidence: 99%
“…The barriers contributing to the inadequacy of this type care described in the literature include lack of education, staff training, care protocols, materials, time, and staff, physical incapacity of the patient (Gibney, Wright, Sharma, & Naganathan, 2015), and the low prioritizing of this care in relation to other nursing care (Nogueira & Jesus, 2017). In addition, many nursing professionals consider oral hygiene as only a hygiene and comfort measure.…”
Section: Introductionmentioning
confidence: 99%
“…Outro agravante é que a Pneumonia hospitalar aumenta a permanência hospitalar em 7 a 9 dias, o custo da internação em 5.800 dólares por paciente, sendo a mortalidade elevada, em torno de 16,0% a 37,0%, podendo chegar a 70,0% nos casos determinados por infecção por Pseudomonas. 8 Com isso, é sabido que cada milímetro cúbico de biofilme dental contém cerca de 100 milhões de microorganismos (bactérias, fungos e vírus), que podem servir como patógenos em potencial 9 . Dentes e gengivas apresentam um reservatório para os patógenos respiratórios e como consequência disso, pacientes internados em UTI apresentam maior risco de desenvolver pneumonia nosocomial.…”
unclassified